2015
DOI: 10.1071/fp15019
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and biochemical changes induced by salt stress in Jatropha curcas seeds during germination and seedling development

Abstract: Jatropha curcas L. is a multipurpose species of the Euphorbiaceae family that is widespread in arid and semiarid regions. This study investigated the ultrastructural and biochemical changes induced by salt stress during J. curcas seed germination and seedling development. Salt stress negatively affected seed germination and increased Na+ and Cl– contents in endosperms and embryo-axis. Lipids represented the most abundant reserves (64% of the quiescent seed dry mass), and their levels were strongly decreased at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
3
17
0
1
Order By: Relevance
“…Similar results were found by other authors, such as Alencar et al (2015), who observed delay in the reserve mobilization during the germination of Jatropha curcas seeds submitted to salt stress. The metabolic processes of lipid degradation can be highly sensitive to stresses, such as water deficit, salinity, among others (KRASENSKY & JONAK, 2012).…”
Section: Resultssupporting
confidence: 81%
“…Similar results were found by other authors, such as Alencar et al (2015), who observed delay in the reserve mobilization during the germination of Jatropha curcas seeds submitted to salt stress. The metabolic processes of lipid degradation can be highly sensitive to stresses, such as water deficit, salinity, among others (KRASENSKY & JONAK, 2012).…”
Section: Resultssupporting
confidence: 81%
“…Some authors have reported the negative effect on germination of seeds subjected to saline stress, such as for pinhão-manso (Alencar et al, 2015) and cajueiro anão precoce (Voigt et al, 2009;Marques et al, 2013). In addition to the negative effect on the germination parameters, these authors also mentioned that the exposure to saline stress contributes to delay of the mobilization of reserves, which compromises the development of the seedlings, affecting their development.…”
Section: Methodsmentioning
confidence: 99%
“…Physiological responses of plant species to abiotic stresses, such as water and saline stress, have been widely repported by several authors (Munns;Tester, 2008;Voigt et al, 2009;Marques et al, 2013;Alencar et al, 2015). The physiological mechanisms of tolerance to these stresses have been studied in plant species during the germinative phase (Voigt et al, 2009, Marques et al, 2013, Alencar et al, 2015.…”
Section: Piptadenia Stipulacea Mimosa Caesalpiniifolia Benth Caesalmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cereus jamacaru, Alencar et al (2012) discovered that lipids were the main reserve in seeds that were stored in cotyledons while soluble sugar and starch were the minor reserves. In Jatropha curcas seeds, it was determined that the endosperm lipids represent the most abundant reserve and proteins were the secondmost important reserve (Alencar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%